Insights into the Role of Inflammation in the Management of Atherosclerosis - Rocha VZ; Rached FH; Miname MH (Dove Medical Press, 2023)
Viviane Zorzanelli Rocha,1,2,* Fabiana Hanna Rached,1,3,* Marcio Hiroshi Miname1,* 1Cardiopneumology Department at the Heart Institute (InCor), University of São Paulo Medical School Hospital (FMUSP), Sao Paulo, Brazil; 2Fleury Medicina e Saúde, Grupo Fleury, São Paulo, SP, Brazil; 3Department of Cardiology, Hospital Israelita Albert Einstein, São Paulo, Brazil*These authors contributed equally to this workCorrespondence: Viviane Zorzanelli Rocha, Fleury Medicina e Saúde, Grupo Fleury, São Paulo, SP, Brazil, Email viviane.rocha@grupofleury.com.brAbstract: Atherosclerosis is the biological basis of ischemic heart disease and ischemic stroke, the leading causes of death in the world. After decades of studies, the understanding of atherosclerosis has evolved dramatically, and inflammation has been recognized as one of the most relevant pillars in all phases of atherosclerotic disease. Nevertheless, only recently, the trial CANTOS, and subsequent outcome studies with colchicine, finally provided proof-of-concept evidence that anti-inflammatory therapies were able to reduce cardiovascular events with no influence on lipid levels. These landmark studies inaugurated an era of clinical and pre-clinical studies of immunomodulatory strategies focused on reduction of cardiovascular risk. Although there are promising results in the field, selection of the most appropriate immunomodulatory therapy and identification of patients who could benefit the most, are still enormous challenges. Further research is imperative before we can finally advance towards regular use of anti-inflammatory agents to reduce atherosclerotic events in our clinical practice.Keywords: inflammation, atherosclerosis, anti-inflammatory therapies, cardiovascular risk